Improving textural properties of gluten‐free veggie sausage with egg white proteins. Issue 3 (11th October 2022) - Zhao, Hefei; Han, Aiyun; Nduwamungu, Joshua J.; Nishijima, Noriaki; Oda, Yoshifumi; Handa, Akihiro; Zhang, Yue; Majumder, Kaustav; Xu, Changmou
Abstract: Gluten and gums are usually used in veggie sausage for textural purposes; however, they are not label‐friendly for consumers with gluten sensitivity or consumers looking for clean‐label foods. Therefore, two commercial egg white proteins (P110 and M200) were studied at different levels (0%–10%) to substitute gluten or xanthan gum. The veggie sausages were subjected to color, texture, length, and weight loss evaluations. M200 significantly improved the texture of sausages and exhibited the most similar texture profile as a commercial meat sausage. The overall texture‐enhanced capability of gel materials was ranked in the order of 5% M200 > 5% P110 ≥ 3% Gluten ≥ 1.3% Xanthan Gum. Egg white proteins did not significantly affect the color, length, and weight loss of sausages. Raman spectra revealed that M200 gel had a higher α‐helix structure than P110 gel, which indicated that M200 formed an ordered gel by reforming tyrosine at Raman shift 833 and 860 cm −1 inside while P110 formed a disordered gel by exposing tyrosine. This study demonstrated that M200 would substitute both the gluten and xanthan gum for improving the texture of veggie sausages. The findings may also be applied to other meat analogs targeting gluten‐free and label‐friendly purposes. Abstract : This study reported two commercial egg white proteins (P110 and M200) to substitute gluten or xanthan gum in veggie sausages. Study shown M200 could substitute both the gluten and xanthan gum for improving the texture of veggie sausages.